Social support and pregnancy attitudes among youth experiencing homelessness. (June 2020) - Begun, Stephanie; Barman-Adhikari, Anamika; O'Connor, Carolyn; Rice, Eric
Highlights: Youth experiencing homelessness demonstrate high rates of pregnancy. Many youth experiencing homelessness endorse pro-pregnancy attitudes. Youths' attitudes may be shaped by their lack of access to needed social supports. This study examined youths' social supports and their pregnancy attitudes. Receipt of monetary support from a serious partner predicted pro-pregnancy attitudes. Pregnancy prevention efforts rooted in youths' social networks are needed. Abstract: Youth experiencing homelessness demonstrate high rates of pregnancy and pregnancy involvement. Many homeless youth view pregnancies positively; some extant research has depicted this group's pro-pregnancy attitudes as a function of youth being in desperate need of resources, such as money, food, clothing, housing, and healthcare. Several studies report that female homeless youth, in particular, feel trapped by their need for monetary resources. Their lack of economic capital may thus cause some of them to go to great lengths, including becoming pregnant, merely to maintain access to supports, especially when pregnancy is perceived as desired by a partner who provides such benefits. However, knowledge of the association between youths' receipt of specific sources and types of social support and their pregnancy attitudes is limited. Social network data were collected from 1003 homeless youth (ages 13–25). Logistic regressions assessed whether specific forms of social support (informational, instrumental, emotional), provided by youths' social network members (street-based peers, home-based peers, family members, service providers, serious partners), are associated with youths' pro-pregnancy attitude endorsements. Multivariate results demonstrated that youth who reported receipt of instrumental support (e.g., monetary resources) from a serious partner were significantly more likely to endorse pro-pregnancy attitudes compared to their peers who did not receive such form of support. Findings suggest a need for creating dyadic communication and prevention activities that facilitate homeless youths' conversations about their economic resource needs, as part of discussions about their pregnancy motivations and relationship goals, in ways that foster informed, self-determined reproductive health decision-making.